PENGEMBANGAN MODEL PEMBIMBINGAN UNTUK MENINGKATKAN KEMAMPUAN GURU DALAM MELAKUKAN REFLEKSI PEMBELAJARAN : Suatu Studi pada Program S1 PGSD Universitas Terbuka - JULAEHA, Siti (2010)
Refleksi pembelajaran membantu meningkatkan kemampuan profesional gu¬ru. Un¬tuk me-ngembangkan dan me¬ningkatkan ke¬mam¬puan me¬¬lakukan refleksi pem¬¬bel¬a¬jar¬an di atas kemampuan yang sudah di¬mi¬liki, ban¬tuan ahli dan du¬kung¬¬an pro¬¬fe¬¬sional di¬perlukan guru. Penelitian ini menjawab masalah "mo¬del pem¬¬bimbingan ba¬gai¬mana yang te¬¬pat un¬¬tuk me¬ning-katkan kemampuan guru me¬la¬ku¬kan ref¬lek¬si pem¬bel¬a¬jar¬¬an?". Pe¬ne¬li¬ti¬an ini dilaksanakan untuk menghasilkan dan mem¬va¬lidasi model pem¬bim¬¬bingan yang da¬pat diterapkan untuk membantu me¬ning¬kat¬kan kemampuan guru me¬¬lakukan ref¬lek¬si pembelajaran. Pen¬de¬kat¬¬an yang di¬gu¬na¬kan dalam penelitian ini ada¬¬lah penelitian dan pe¬ngembangan (R & D) dengan ta¬hap-tahap: studi pen-da¬hu¬lu¬an melalui survai dan studi pustaka, pe¬ngem¬¬bangan mo¬del melalui penelitian tindakan dan evaluasi pada uji la¬pang¬an ter¬ba¬tas dan meluas, serta uji validasi melalui eks¬pe¬ri¬men-kuasi. Pe¬¬ne¬-litian ini di¬la¬ku¬kan pada Program S1 PGSD Uni¬versitas Terbuka de¬ngan subjek pe¬¬ne¬¬litian guru-ma¬hasiswa dan supervisor PKP di wilayah UPBJJ-UT Ban¬dung. Pe¬¬¬ngumpulan data dilakukan dengan studi do¬ku¬mentasi, desk evaluation, ang¬¬ket, wawancara, ob¬ser¬¬va¬si, dan tugas pembuatan tulisan refleksi. Data di¬ana¬li¬sis se¬¬¬ca¬ra des¬krip¬¬tif kualitatif dan kuantitatif dengan peng¬hi¬tung¬an rerata dan per¬sen¬ta¬se ser¬ta ana¬li¬sis statistika non-parametrik Wilcoxon Signed Rank Test dan Mann-Whitney U-Test. Temuan penelitian menunjukkan bahwa Model Pem¬bimbingan Ref¬leksi Pem¬bel¬ajaran yang di¬da¬sarkan pa¬¬¬da teori konstruktivisme so¬¬sial serta ber¬¬kaitan dengan ide communities of practice dan pendekatan supervisi kli¬¬nis ter¬buk¬ti efektif dalam me¬ning¬katkan skor tulisan refleksi guru-ma¬¬hasiswa S1 PGSD-UT. Model Pem¬bim¬bing¬an Refleksi Pembelajaran diterapkan melalui lang¬kah ori¬en¬tasi, eks¬plorasi, in¬¬ter¬pre¬tasi, dan re-desain dengan penekanan pada pe¬mo¬del¬an, kegiatan berbagi, praktek ter¬bimbing dan mandiri, serta latihan pembuatan tu¬lis-an ref¬leksi secara berke¬si¬nam¬bung¬an. Mo¬del Pembimbingan Refleksi Pem¬bel¬a¬jaran da¬pat dijadikan model pem¬bim¬bingan al¬ternatif dalam membantu me¬ning¬kat¬kan ke¬mam¬puan guru melakukan ref¬leksi pem¬bel¬ajaran. Untuk dapat menerapkan model ini secara efektif, Program S1 PGSD hendaknya menyediakan panduan, bahan belajar program video, dan layanan bel¬ajar online serta sosialisasi, pelatihan, dan monitoring penerapan model. Selain itu, temuan pe¬ne¬litian ini me¬¬munculkan beberapa per¬tanyaan yang me¬merlukan pene¬li¬ti¬an lebih lan¬jut ABSTRACT Teaching reflection can improve teachers' professional abilities. In order to undertake reflective practice that is beyond the present level of their abilities, expert's helps and professional support are needed by teachers. This study was designed to find out "a supervisory meeting model that is appropriate for facilitating teachers to enhance their ability in teaching reflection". Accordingly, the research objectives are to develop and validate a supervisory meeting model that can improve teachers' ability in conducting teaching reflection. An approach used in this study was a research and development approach consisting the preliminary study through a survey and a literature study, the model development through an action research and an evaluation at limited and broader field testing, and the validation testing through a quasi-experiment. This study was taken place at The S1 PGSD Program at the Indonesian Open Learning University and the research subject was student-teachers who took the Professional Capability Development (PCD/PKP) course and PKP supervisors at the Bandung regional center. Data collection techniques used in the study were document studies, desk evaluation, questionnaires, interviews, observations, and assignments of making reflective writings. Those data were analyzed by quantitative (mean, percentage, and non-parametric statistics: Wilcoxon Signed Rank Test and Mann-Whitney U-Test) as well as qualitative descriptive techniques. Research findings showed that the Model of Supervisory Meeting for Teaching Reflection that was developed based on a social constructivist theory and embedded with the idea of communities of practice and a clinical supervision approach was proved to be effective for increasing reflective writings scores of student-teachers of S1 PGSD Program. The Model of Supervisory Meeting for Teaching Reflection was applied through orientation, exploration, interpretation, and re-design activities with emphasizing on modeling, sharing, guided- and self-directed practicing, as well as taking continuous exercise writing reflective journals. The Model of Supervisory Meeting for Teaching Reflection can be an alternative model in fostering teachers' ability in conducting teaching reflection. In order to effectively implement this model, the S1 PGSD Program should develop manuals, video program, and online tutorial, as well as provide socialization of, training in, and monitoring the implementation of model in tutorial process. In addition, the findings of this study pose questions which demand further study.